Care Facilitation Advances Movement Along the Hepatitis C Care Continuum for Persons With Human Immunodeficiency Virus, Hepatitis C, and Substance Use: A Randomized Clinical Trial (CTN-0064). (27th June 2021) - Metsch, Lisa R; Feaster, Daniel J; Gooden, Lauren K; Masson, Carmen; Perlman, David C; Jain, Mamta K; Matheson, Tim; Nelson, C Mindy; Jacobs, Petra; Tross, Susan; Haynes, Louise; Lucas, Gregory M; et al.
Abstract: Background: Direct-acting antivirals can cure hepatitis C virus (HCV). Persons with HCV/HIV and living with substance use are disadvantaged in benefiting from advances in HCV treatment. Methods: In this randomized controlled trial, participants with HCV/HIV were randomized between February 2016 and January 2017 to either care facilitation or control. Twelve-month follow-up assessments were completed in January 2018. Care facilitation group participants received motivation and strengths-based case management addressing retrieval of HCV viral load results, engagement in HCV/HIV care, and medication adherence. Control group participants received referral to HCV evaluation and an offer of assistance in making care appointments. Primary outcome was number of steps achieved along a series of 8 clinical steps (eg, receiving HCV results, initiating treatment, sustained virologic response [SVR]) of the HCV/HIV care continuum over 12 months postrandomization. Results: Three hundred eighty-one individuals were screened and 113 randomized. Median age was 51 years; 58.4% of participants were male and 72.6% were Black/African American. Median HIV-1 viral load was 27 209 copies/mL, with 69% having a detectable viral load. Mean number of steps completed was statistically significantly higher in the intervention group vs controls (2.44 vs 1.68 steps; χ  2 [1] = 7.36, P  = .0067). Men in the intervention group completed a statistically significantly higher number of steps than controls. Eleven participants achieved SVR with no difference by treatment group. Conclusions: The care facilitation intervention increased progress along the HCV/HIV care continuum, as observed for men and not women. Study findings also highlight continued challenges to achieve individual-patient SVR and population-level HCV elimination. Clinical Trials Registration: NCT02641158. Abstract : In this era of direct-acting antivirals that can cure hepatitis C virus (HCV) infection in 1–3 months, a short-term care facilitation intervention for persons living with HIV and HCV who use drugs is efficacious in making meaningful advances toward HCV cure.